Preparation method of water-based UV curing conductive ink

Through the synergistic effect of composite materials and the new UV curing system, the conductivity, adhesion and flexibility of conductive inks are improved, and the performance of conductive inks is degraded during storage and application is solved, and the adaptability and long-term stability to flexible substrates are achieved.

CN119614021APending Publication Date: 2025-03-14SUZHOU OLES ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202510004356.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During storage and application, existing conductive inks are prone to decline in conductivity due to condensation and agglomeration, and high-temperature sintering is not suitable for flexible substrates, and the active chemical properties of silver affect long-term stability.

Method used

Improve silver ion conductivity through composite materials synergistic effects and design a new UV curing system to improve the adhesion and flexibility of ink. Specific solutions include preparing modified aqueous UV resin, nanosilver and nanosilver-graphene composite materials, and performing UV curing after mixing.

Benefits of technology

The high-performance conductivity, adhesion and flexibility of conductive ink are achieved, the problems of degraded conductivity and flexible substrate adaptability are solved, and the long-term stability of ink is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226423900000021
    Figure BDA0005226423900000021
  • Figure BDA0005226423900000051
    Figure BDA0005226423900000051
  • Figure BDA0005226423900000052
    Figure BDA0005226423900000052
Patent Text Reader

Abstract

The invention provides a preparation method of water-based UV curing conductive ink, and relates to the technical field of polymer conductive material preparation, the preparation method comprises the following steps: respectively preparing modified water-based UV resin, nano-silver and a nano-silver-graphene composite material; and mixing the prepared modified water-based UV resin, nano-silver and a nano-silver-graphene composite material with a photoinitiator, 1, 6-hexanediol diacrylate and an auxiliary agent to obtain the water-based UV curing conductive ink. The preparation method comprises the following steps: firstly, synthesizing an unsaturated epoxy intermediate (EA) by utilizing acrylic acid (AA) and bisphenol A type epoxy resin E-51, then adding the epoxy intermediate EA into an intermediate PUA, and carrying out full end capping on the PUA to prepare light-cured resin; preparing nano-silver and a nano-silver-graphene composite material through a chemical reduction method; and finally, constructing a conductive network in the ink by virtue of a synergistic effect between the nano-silver and the nano-silver-graphene composite material, so as to prepare the water-based UV-cured high-performance conductive ink.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a method for preparing water-based UV-curable conductive ink, and relates to the technical field of polymer conductive material preparation. Background Art

[0002] In recent years, electronic printing technology has attracted widespread attention in many fields due to its low cost, environmental protection, suitability for low-temperature processing and large-scale production. The core of this technology lies in the development of conductive inks, especially the application of metal nanomaterials. Nanosilver particles have become an important component of conductive inks due to their excellent conductivity and relatively low resistivity. However, conductive inks using silver nanoparticles still face some significant challenges in their applications. During storage, silver nanoparticles are prone to condensation and agglomeration due to van der Waals forces. This will cause the particle size to increase, thereby affecting the rheological properties and conductive properties of the ink. Silver nanoparticles usually require high-temperature sintering to achieve good conductivity and adhesion. However, high-temperature treatment is often not suitable for flexible substrates, which limits its scope of application. Silver has active chemical properties and is prone to oxidation reactions. This not only affects the conductive properties, but also leads to a decrease in the long-term stability of the ink. At present, researchers have tried to solve the above-mentioned problems through various means. Prevent the condensation and agglomeration of nanoparticles by surface modification technology or adding stabilizers. Common methods include coating organic molecules or polymers on the surface of particles to form a protective layer to increase the dispersion stability of particles. Develop low-temperature sintering methods, such as photo-sintering, plasma sintering, or laser sintering. These technologies achieve sintering at low temperatures by local heating or rapid heating to protect flexible substrates. Explore other conductive materials, such as copper, graphene, or carbon nanotubes, as alternatives to silver. These materials may provide a lower-cost conductive ink solution with similar performance. Add antioxidants or protective chemicals to the ink to reduce the oxidation rate of silver and improve its environmental stability. Although a variety of methods have been used to improve the stability of nanosilver inks, the stability and reliability of their performance during long-term storage and use still need to be further verified and optimized. The compatibility of inks with different substrates and their functional integration in practical applications remain challenges, especially in multi-layer circuits or flexible electronics. Although alternative materials have alleviated some of the problems, they also give up the advantages of the replaced materials. Emerging low-temperature sintering technologies may increase process complexity and equipment costs, and need to be further simplified and optimized to adapt to industrial production. During the printing process, it is still challenging to ensure the uniform distribution of nanoparticles in the ink, which directly affects the continuity and performance of the conductive path.

[0003] The paper "UV crosslinkable emulsions with silver nanoparticles for inkjet printing of conductive 3D structures" discloses an oil-in-water emulsion type UV curable conductive ink containing silver nanoparticles. This ink forms a solid structure under ultraviolet light, and the silver nanoparticles are sintered at room temperature by contact with NaCl solution, with high conductivity; the paper uses oil-in-water emulsion, focusing on the study of interface control technology and room temperature sintering strategy, and does not pay attention to the mechanical properties of the ink such as flexibility and adhesion.

[0004] Overall, although conductive ink technology has shown great potential in electronic printing, there are still many technical and economic issues to be solved in commercial applications. Future research directions include the exploration of new materials, process optimization, and sustainable development solutions. Summary of the invention

[0005] To solve the above problems, the present invention is characterized in that the conductivity of silver ions is improved through the synergistic effect of composite materials, and a new UV curing system is designed to improve the adhesion and flexibility of the ink. The specific scheme is as follows:

[0006] A method for preparing a water-based UV-curable conductive ink comprises the following steps:

[0007] S1, preparing modified waterborne UV resin, nanosilver and nanosilver-graphene composite materials respectively;

[0008] S2, taking the prepared modified water-based UV resin, nanosilver and nanosilver-graphene composite material, mixing them with a photoinitiator, 1,6-hexanediol diacrylate and an additive to obtain a water-based UV curable conductive ink;

[0009] Among them, the structure of the modified waterborne UV resin prepared by S1 is:

[0010]

[0011] From left to right, R1 and R2 are six-membered rings containing a central carbon atom and four connected methylene groups (CH2) to form a stable molecular skeleton. R3 is the bisphenol A group, which is the central part of the bisphenol A molecular structure and contains two aromatic groups and a secondary carbon bridge (two methyl groups -CH3).

[0012] Preferably, the auxiliary agent in step S2 includes one or more of gas silica, coupling agent KH-560, defoamer BYK-1794, dispersant BYK-431, leveling agent BYK-UV-3510, leveling agent BYK-333, and DEGO-4100 wetting and leveling agent; the photoinitiator includes Darocur 1173 or Irgacure 2959.

[0013] Preferably, among the components described in step S2, nanosilver accounts for 0-60wt% of the total mass; the nanosilver-graphene composite material accounts for 0-60wt% of the total mass; 1,6-hexanediol diacrylate accounts for 10-15wt% of the total mass; the photoinitiator accounts for 3-5wt% of the total mass, and the auxiliary agent accounts for 0.5-5wt% of the total mass; the remainder is modified water-based UV resin.

[0014] Preferably, the method for preparing the modified waterborne UV resin in step S1 comprises:

[0015] (1) Preparing a modified epoxy resin prepolymer: adding a catalyst to a resin, mixing well, heating, slowly dropping a modifier into the system to carry out reaction I, cooling after the reaction is completed, and obtaining a modified epoxy resin prepolymer;

[0016] (2) Synthesis of water-based UV resin: polycaprolactone diol, catalyst and chain extender are mixed and heated to carry out reaction II; after the reaction is completed, the temperature is lowered, pentaerythritol triacrylate and catalyst are added, and the temperature is kept to carry out reaction III; modified epoxy resin prepolymer is added and the reaction is continued until the isocyanate group content is constant; and post-treatment is performed to obtain a modified water-based UV resin.

[0017] Preferably, the resin in step (1) of the method for preparing a modified water-based UV resin includes one or more of epoxy resin-E51, polyurethane, phenolic resin, and acrylic resin; wherein the epoxy resin includes one or more of bisphenol A epoxy resin, phenolic epoxy resin, and glycidyl ether epoxy resin; the epoxy resin specifically includes one or more of epoxy resin E-12, epoxy resin E-20, epoxy resin E-44, epoxy resin E-51, epoxy resin F-44, and epoxy resin F-51.

[0018] Preferably, the catalyst in step (1) of the method for preparing a modified waterborne UV resin comprises one or more of tetrabutylammonium bromide, dibutyltin dilaurate, stannous octoate, organic lead, and organic zinc compounds.

[0019] Preferably, the modified substance in step (1) of the method for preparing a modified waterborne UV resin comprises one or more of acrylic acid (AA), polypropylene, polyurethane (PU), bisphenol A epoxy resin (E-51), and silicone oil.

[0020] Preferably, in the method for preparing modified waterborne UV resin, the amount of epoxy resin and acrylic acid in step (1) is equal; the amount of catalyst used is 0.3-0.5wt% of the sum of the mass of epoxy resin and acrylic acid.

[0021] Preferably, in the method for preparing modified waterborne UV resin, the slow dripping in step (1) has a dripping time of 1-3 hours, and the heat preservation reaction time after the dripping is 3-5 hours; the reaction temperature is 70-90°C.

[0022] Preferably, the chain extender in step (2) of the method for preparing a modified waterborne UV resin comprises one or more of dimethylolbutyric acid, ethylene glycol, propylene glycol, and stearic acid.

[0023] Preferably, the catalyst in step (2) of the method for preparing a modified waterborne UV resin comprises one or more of isophorone diisocyanate, sulfuric acid, sodium persulfate, pentaerythritol triacrylate, and dibutyltin dilaurate.

[0024] Preferably, in the method for preparing modified waterborne UV resin, the temperature of reaction II in step (2) is 70-80°C and the time is 2-3h; the temperature of reaction III is 50-55°C and the time is 4-5h.

[0025] Preferably, in the method for preparing a modified waterborne UV resin, the amount of the catalyst in step (2) is 0.3-0.5wt% of the mass of the system at that time; the amount of the chain extender is 5-10wt% of the polycaprolactone diol; the amount of the pentaerythritol triacrylate is 10-20wt% of the polycaprolactone diol; and the amount of the modified epoxy resin prepolymer is 0.2-5 times the mass of the polycaprolactone diol.

[0026] Preferably, the post-treatment in step (2) of the method for preparing the modified waterborne UV resin comprises: adding a diluent and mixing, then adding a neutralizer for neutralization, adding deionized water for uniform dispersion, and removing the solvent by reduced pressure distillation to obtain the modified waterborne UV resin.

[0027] Preferably, the diluent includes one or more of acetone, methanol and benzene; the neutralizer includes one or more of triethylamine, ethylenediamine and ferric chloride; and the neutralization time is 0.5-1h.

[0028] Preferably, the amount of the diluent added is 5-30wt% of the mass of the system at that time; the amount of the neutralizer added is 0.1-5wt% of the mass of the system at that time; and the amount of deionized water added is 10-50wt% of the mass of the system at that time.

[0029] Preferably, the method for preparing the nano silver-graphene composite material in step S1 comprises:

[0030] Prepare graphene oxide into a suspension, add silver nitrate aqueous solution into the graphene oxide suspension and mix well, add a protective agent and a reducing agent while stirring in a constant temperature water bath, continue stirring, cool and centrifuge to obtain a precipitate, wash the precipitate with anhydrous ethanol, and disperse it in anhydrous ethanol to obtain a nanosilver-graphene dispersion.

[0031] Preferably, in the graphene oxide dispersion, the graphene oxide content is 2-4 mg / mL; the concentration of the silver nitrate aqueous solution is 0.05-0.15 mol / L, the molar ratio of the mixed silver nitrate and graphene oxide is 1:10, the molar ratio of the protective agent to the silver nitrate is (1.5-2):1; the molar ratio of the reducing agent to the silver nitrate is (0.5-1):1; the constant temperature water bath temperature is 50-65°C, and the continuous stirring time is 0.5-1h; the centrifugation is performed at 12000-15000rpm for 10-15min.

[0032] Preferably, the method for preparing nanosilver in step S1 comprises:

[0033] Slowly add silver nitrate aqueous solution to the mixed solution of protective agent and reducing agent, stir in a constant temperature water bath until the solution changes to gray, centrifuge to obtain precipitate, wash the precipitate with anhydrous ethanol, and disperse it in anhydrous ethanol to obtain a nanosilver dispersion.

[0034] Preferably, the concentration of the silver nitrate aqueous solution is 0.05-0.15 mol / L; the molar ratio of the protective agent to the silver nitrate is (1.5-2.0):1; the molar ratio of the reducing agent to the silver nitrate is (0.5-1):1; the constant temperature water bath temperature is 50-65°C; the centrifugation is performed at 12000-15000 rpm for 10-15 min.

[0035] Preferably, the reducing agent includes one or more of hydrazine hydrate, sodium sulfite, sodium hydroxide, sodium borohydride, and potassium iodide; the protecting agent includes one or more of polyvinyl pyrrolidone, sodium bisulfate, and alkaline ammonia water.

[0036] Beneficial effects of the present invention:

[0037] The present invention firstly utilizes acrylic acid (AA) and bisphenol A epoxy resin E-51 to synthesize an unsaturated epoxy intermediate (EA), then adds the epoxy intermediate EA into the intermediate PUA, fully caps the PUA, and prepares a photocurable resin; prepares nanosilver and nanosilver-graphene composite materials by a chemical reduction method; finally, through the synergistic effect between the nanosilver and the nanosilver-graphene composite materials, constructs a conductive network inside the ink, and prepares a water-based UV-curable high-performance conductive ink. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Schematic diagram of the conductive pathway of nanosilver and nanosilver-graphene composite materials.

[0039] Figure 2 This is the infrared spectrum of the prepolymer EA prepared in the embodiment of the present invention;

[0040] Figure 3 This is the infrared spectrum of the water-based UV resin prepared in the embodiment of the present invention;

[0041] Figure 4 The XRD spectrum of the nanosilver prepared in the embodiment of the present invention;

[0042] Figure 5 This is the XRD spectrum of the nanosilver-graphene composite material prepared in the embodiment of the present invention. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0045] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0046] Embodiment A method for preparing a water-based UV curable conductive ink comprises the following steps:

[0047] S1, preparing modified waterborne UV resin, nanosilver and nanosilver-graphene composite materials respectively;

[0048] S2, taking the prepared modified water-based UV resin, nanosilver and nanosilver-graphene composite material, mixing them with a photoinitiator, 1,6-hexanediol diacrylate and an additive to obtain a water-based UV curable conductive ink;

[0049] Among them, the structure of the modified waterborne UV resin prepared by S1 is:

[0050]

[0051] From left to right, R1 and R2 are six-membered rings containing a central carbon atom and four connected methylene groups (CH2) to form a stable molecular skeleton. R3 is the bisphenol A group, which is the central part of the bisphenol A molecular structure and contains two aromatic groups and a secondary carbon bridge (two methyl groups -CH3).

[0052] The auxiliary agent in step S2 includes one or more of the following: gas silica, coupling agent KH-560, defoaming agent BYK-1794, dispersant BYK-431, leveling agent BYK-UV-3510, leveling agent BYK-333, DEGO-4100 wetting and leveling agent; the photoinitiator includes Darocur 1173 or Irgacure 2959.

[0053] Among the components described in step S2, nanosilver accounts for 0-60wt% of the total mass; the nanosilver-graphene composite material accounts for 0-60wt% of the total mass; 1,6-hexanediol diacrylate accounts for 10-15wt% of the total mass; the photoinitiator accounts for 3-5wt% of the total mass, and the auxiliary agent accounts for 0.5-5wt% of the total mass; the remainder is modified water-based UV resin.

[0054] The method for preparing the modified waterborne UV resin in step S1 comprises:

[0055] (1) Preparation of modified epoxy resin prepolymer: Add a catalyst to the resin, mix well and then heat, slowly drop the modifier into the system to carry out reaction I, cool down after the reaction to obtain a modified epoxy resin prepolymer. The reaction diagram is as follows:

[0056]

[0057] The process includes the following: Activation of epoxy groups: Tetrabutylammonium bromide is used as a phase transfer catalyst, and its main function is to accelerate the activation of epoxy groups. The epoxy groups in the epoxy resin E-51 are activated under the action of the catalyst, which increases the reaction activity. Nucleophilic addition of acrylic acid: The carboxyl group in acrylic acid (AA) carries out nucleophilic attack on the epoxy groups in the epoxy resin. Under the condition of 90°C, the carboxyl group of AA undergoes a ring-opening reaction on the epoxy group in the epoxy resin to form a hydroxyl group and an ester bond. Prepolymer formation: Slowly add an equimolar amount of acrylic acid within 1 hour to ensure the controllability and uniformity of the reaction. Subsequently, the reaction is continued under insulation for 3 hours, so that the reaction between acrylic acid and epoxy resin is sufficient, and finally a prepolymer (EA) with an acrylate structure is obtained.

[0058] (2) Synthesis of water-based UV resin: polycaprolactone diol, catalyst and chain extender are mixed and heated to carry out reaction II; after the reaction is completed, the temperature is lowered, pentaerythritol triacrylate and catalyst are added, and the temperature is kept to carry out reaction III; modified epoxy resin prepolymer is added, and the reaction is continued until the isocyanate group content is constant; post-treatment is carried out to obtain modified water-based UV resin. The reaction diagram is as follows:

[0059]

[0060] IPDI reacts with the isocyanate (–NCO) in PCL and the polycaprolactone diol (–OH) to form the urethane bonds (–NHCOO–) of the polyurethane. The hydroxyl groups in DMBA continue to react with the isocyanate groups (–NCO) in the prepolymer to further extend the molecular chain and generate more urethane bonds. The multifunctional acrylate groups of PETA are connected to the polyurethane backbone by reacting with the isocyanate groups in the system. This allows the introduction of double bonds for subsequent ultraviolet curing (UV curing). The acrylate groups in the prepolymer EA can react with the isocyanate groups in the system to further enhance the UV curing ability and improve the cross-linking structure of the system. PA is used to adjust the viscosity of the system to make it easier to process. TEA (aminotriethanol): As an alkaline neutralizer, it reacts with the carboxyl groups in DMBA to form ammonium salts, so that the prepolymer becomes a water-soluble or water-dispersible polyurethane.

[0061] The resin in step (1) of the method for preparing a modified water-based UV resin includes one or more of epoxy resin-E51, polyurethane, phenolic resin, and acrylic resin; wherein the epoxy resin includes one or more of bisphenol A epoxy resin, phenolic epoxy resin, and glycidyl ether epoxy resin; the epoxy resin specifically includes one or more of epoxy resin E-12, epoxy resin E-20, epoxy resin E-44, epoxy resin E-51, epoxy resin F-44, and epoxy resin F-51.

[0062] The catalyst in step (1) of the method for preparing modified waterborne UV resin includes one or more of tetrabutylammonium bromide, dibutyltin dilaurate, stannous octoate, organic lead and organic zinc compounds.

[0063] In the method for preparing modified waterborne UV resin, the modified substance in step (1) includes one or more of acrylic acid (AA), polypropylene, polyurethane (PU), bisphenol A epoxy resin (E-51), and silicone oil.

[0064] In the method for preparing modified waterborne UV resin, the amount of epoxy resin and acrylic acid in step (1) is equal; the amount of catalyst used is 0.3-0.5wt% of the sum of the mass of epoxy resin and acrylic acid.

[0065] In the method for preparing modified waterborne UV resin, the slow dripping in step (1) has a dripping time of 1-3 hours, and the heat preservation reaction time after the dripping is 3-5 hours; the reaction temperature is 70-90°C.

[0066] The chain extender in step (2) of the method for preparing a modified waterborne UV resin comprises one or more of dimethylolbutyric acid, ethylene glycol, propylene glycol, and stearic acid.

[0067] The catalyst in step (2) of the method for preparing a modified waterborne UV resin comprises one or more of isophorone diisocyanate, sulfuric acid, sodium persulfate, pentaerythritol triacrylate, and dibutyltin dilaurate.

[0068] In the method for preparing modified waterborne UV resin, the temperature of reaction II in step (2) is 70-80°C and the time is 2-3h; the temperature of reaction III is 50-55°C and the time is 4-5h.

[0069] In the method for preparing a modified waterborne UV resin, the amount of the catalyst in step (2) is 0.3-0.5wt% of the mass of the system at that time; the amount of the chain extender is 5-10wt% of the polycaprolactone diol; the amount of the pentaerythritol triacrylate is 10-20wt% of the polycaprolactone diol; and the amount of the modified epoxy resin prepolymer is 0.2-5 times the mass of the polycaprolactone diol.

[0070] The post-treatment in step (2) of the method for preparing a modified waterborne UV resin comprises: adding a diluent and mixing, then adding a neutralizer for neutralization, adding deionized water for uniform dispersion, and removing the solvent by reduced pressure distillation to obtain a modified waterborne UV resin.

[0071] The diluent includes one or more of acetone, methanol and benzene; the neutralizer includes one or more of triethylamine, ethylenediamine and ferric chloride; and the neutralization time is 0.5-1h.

[0072] The amount of the diluent added is 5-30wt% of the mass of the system at that time; the amount of the neutralizer added is 0.1-5wt% of the mass of the system at that time; and the amount of deionized water added is 10-50wt% of the mass of the system at that time.

[0073] The method for preparing the nano silver-graphene composite material in step S1 comprises:

[0074] Prepare graphene oxide into a suspension, add silver nitrate aqueous solution to the graphene oxide suspension and mix well, add a protective agent and then add a reducing agent while stirring in a constant temperature water bath, continue stirring, cool and centrifuge to obtain a precipitate, wash the precipitate with anhydrous ethanol, and disperse it in anhydrous ethanol to obtain a nanosilver-graphene dispersion. There are certain gaps between the nanosilver particles, which slows down the increase in the conductivity of the overall water-based UV curing ink. The homemade nanosilver-graphene composite material is used as a conductive filler to solve the defects of nanosilver in conductive inks. By increasing the contact area, more conductive pathways are constructed to improve the conductive performance. The schematic diagram of the conductive pathway is shown in Figure 1 .

[0075] In the graphene oxide dispersion, the graphene oxide content is 2-4 mg / mL; the concentration of the silver nitrate aqueous solution is 0.05-0.15 mol / L, the molar ratio of the mixed silver nitrate and graphene oxide is 1:10, the molar ratio of the protective agent to the silver nitrate is (1.5-2):1; the molar ratio of the reducing agent to the silver nitrate is (0.5-1):1; the constant temperature water bath temperature is 50-65°C, and the stirring time is continued for 0.5-1h; the centrifugation is performed at 12000-15000rpm for 10-15min.

[0076] The method for preparing nanosilver in step S1 comprises:

[0077] Slowly add silver nitrate aqueous solution to the mixed solution of protective agent and reducing agent, stir in a constant temperature water bath until the solution changes to gray, centrifuge to obtain precipitate, wash the precipitate with anhydrous ethanol, and disperse it in anhydrous ethanol to obtain a nanosilver dispersion.

[0078] The concentration of the silver nitrate aqueous solution is 0.05-0.15 mol / L; the molar ratio of the protective agent to the silver nitrate is (1.5-2.0):1; the molar ratio of the reducing agent to the silver nitrate is (0.5-1.0):1; the temperature of the constant temperature water bath is 50-65°C; the centrifugation is 12000-15000rpm, and the centrifugation is 10-15min.

[0079] The reducing agent includes one or more of hydrazine hydrate, sodium sulfite, sodium hydroxide, sodium borohydride, and potassium iodide; the protecting agent includes one or more of polyvinyl pyrrolidone, sodium bisulfate, and alkaline ammonia water.

[0080] Embodiment 1:

[0081] Preparation of acrylic acid modified epoxy resin prepolymer (EA)

[0082] Under a nitrogen atmosphere, add 10 g of epoxy resin E-51 and 0.1028 g of tetrabutylammonium bromide catalyst to a flask equipped with a condenser, a thermometer and a stirring device, and heat to 90°C. Then slowly drop an equal molar amount of 7.2 g of acrylic acid AA into the flask. The addition time is 1.5 h. Keep warm for 4 h. Cool down to obtain a prepolymer (EA) which is stored for later use.

[0083] Water-based UV resin synthesis

[0084] Under a nitrogen atmosphere, 0.04 g of isophorone diisocyanate, 10 g of polycaprolactone diol and 0.5 g of dihydroxymethylbutyric acid with a solid content of 39.89% were added in proportion to a flask equipped with a stirring device, and the mixture was reacted at 80°C for 2 h. The mixture was then cooled to 50°C, 0.05 mol of pentaerythritol triacrylate and dibutyltin dilaurate were added, and the mixture was reacted for 4 h. 5 g of prepolymer EA was added until the isocyanate group content was constant. 3 g of acetone was added to reduce the viscosity of the system, 0.37 g of triethylamine was added for neutralization for 0.5 h, 7.6 g of deionized water was added for dispersion, and the solvent was removed by distillation under reduced pressure to prepare a UV-curable resin.

[0085] Preparation of Nanosilver

[0086] Take an appropriate amount of silver nitrate and dissolve it in 100mL deionized water to prepare a 1mol·L-1 silver nitrate aqueous solution. Dilute the silver nitrate aqueous solution to 0.05moL / L, and slowly add it to a mixed solution of 0.55g PVP and 2.5g hydrazine hydrate using a constant pressure dropping funnel, control the n(PVP) / n(AgNO3) ratio to 1.5:1, and stir in a constant temperature water bath for 0.5h. The solution turns gray, which is the prepared nanosilver solution. Centrifuge the prepared nanosilver at 12000rpm for 15min, wash the centrifuged product several times with anhydrous ethanol, and redissolve the precipitate in ethanol after centrifugation for storage.

[0087] Preparation of Nanosilver-Graphene Composite Materials

[0088] Take the graphene oxide suspension and dilute it to 2 mg / mL with anhydrous ethanol; take an appropriate amount of silver nitrate and dissolve it in 10 mL of deionized water, mix the prepared suspension evenly, and add 0.55 g of PVP. Transfer the mixed solution to a 60°C water bath for stirring, add 2.5 g of hydrazine hydrate while stirring, cool it down, centrifuge it, remove the lower part of the centrifuge tube, and then repeat centrifugation and washing for multiple times to obtain a nanosilver-graphene dispersion.

[0089] Preparation of water-based UV-curable conductive ink (taking 5g as an example)

[0090] Binder: 20wt% homemade UV curable resin (1g), 11wt% 1,6-hexanediol diacrylate (0.55g)

[0091] Conductive filler: 60wt% (nanosilver) (3g)

[0092] Functional additives: 5wt% (BYK-1794 leveling agent, BYK-431 dispersant) (0.25g)

[0093] Photoinitiator: 4 wt% (2% Darocur 1173, 2% Irgacure 2959) (0.2 g)

[0094] A water-based UV-curable conductive ink was prepared according to the above ratio. After being evenly dispersed by a three-roll mill and a high-speed disperser, the ink was left to stand in a light-shielded place to defoam. The ink was then printed on a substrate and tested for performance after UV curing.

[0095] Embodiment 2:

[0096] Preparation of acrylic acid modified epoxy resin prepolymer (EA)

[0097] Same as above-mentioned embodiment 1

[0098] Water-based UV resin synthesis

[0099] Same as above-mentioned embodiment 1

[0100] Preparation of Nanosilver

[0101] Same as above-mentioned embodiment 1

[0102] Preparation of Nanosilver-Graphene Composite Materials

[0103] Same as above-mentioned embodiment 1

[0104] Preparation of water-based UV-curable conductive ink

[0105] Binder: 20wt% homemade UV curable resin (1g), 11wt% 1,6-hexanediol diacrylate (0.55g)

[0106] Conductive filler: 60wt% (50wt% nanosilver, 10wt% nanosilver-graphene composite material) (3g)

[0107] Functional additives: 5wt% (BYK-1794 leveling agent, BYK-431 dispersant) (0.25g)

[0108] Photoinitiator: 4 wt% (2% Darocur 1173, 2% Irgacure 2959) (0.2 g)

[0109] A water-based UV-curable conductive ink was prepared according to the above ratio. After being evenly dispersed by a three-roll mill and a high-speed disperser, the ink was left to stand in a light-shielded place to defoam. The ink was then printed on a substrate and tested for performance after UV curing.

[0110] Embodiment 3:

[0111] Preparation of acrylic acid modified epoxy resin prepolymer (EA)

[0112] Same as above-mentioned embodiment 1

[0113] Water-based UV resin synthesis

[0114] Same as above-mentioned embodiment 1

[0115] Preparation of Nanosilver

[0116] Same as above-mentioned embodiment 1

[0117] Preparation of Nanosilver-Graphene Composite Materials

[0118] Same as above-mentioned embodiment 1

[0119] Preparation of water-based UV-curable conductive ink

[0120] Binder: 20wt% homemade UV curable resin (1g), 11wt% 1,6-hexanediol diacrylate (0.55g)

[0121] Conductive filler: 60wt% (40wt% nanosilver, 20wt% nanosilver-graphene composite material) (3g)

[0122] Functional additives: 5wt% (BYK-1794 leveling agent, BYK-431 dispersant) (0.25g)

[0123] Photoinitiator: 4 wt% (2% Darocur 1173, 2% Irgacure 2959) (0.2 g)

[0124] A water-based UV-curable conductive ink was prepared according to the above ratio. After being evenly dispersed by a three-roll mill and a high-speed disperser, the ink was left to stand in a light-shielded place to defoam. The ink was then printed on a substrate and tested for performance after UV curing.

[0125] Embodiment 4:

[0126] Preparation of acrylic acid modified epoxy resin prepolymer (EA)

[0127] Same as above-mentioned embodiment 1

[0128] Water-based UV resin synthesis

[0129] Same as above-mentioned embodiment 1

[0130] Preparation of Nanosilver

[0131] Same as above-mentioned embodiment 1

[0132] Preparation of Nanosilver-Graphene Composite Materials

[0133] Same as above-mentioned embodiment 1

[0134] Preparation of water-based UV-curable conductive ink

[0135] Binder: 20wt% homemade UV curable resin (1g), 11wt% 1,6-hexanediol diacrylate (0.55g)

[0136] Conductive filler: 60wt% (30wt% nanosilver, 30wt% nanosilver-graphene composite material) (3g)

[0137] Functional additives: 5wt% (BYK-1794 leveling agent, BYK-431 dispersant) (0.25g)

[0138] Photoinitiator: 4 wt% (2% Darocur 1173, 2% Irgacure 2959) (0.2 g)

[0139] A water-based UV-curable conductive ink was prepared according to the above ratio. After being evenly dispersed by a three-roll mill and a high-speed disperser, the ink was left to stand in a light-shielded place to defoam. The ink was then printed on a substrate and tested for performance after UV curing.

[0140] Embodiment 5:

[0141] Preparation of acrylic acid modified epoxy resin prepolymer (EA)

[0142] Same as above-mentioned embodiment 1

[0143] Water-based UV resin synthesis

[0144] Same as above-mentioned embodiment 1

[0145] Preparation of Nanosilver

[0146] Same as above-mentioned embodiment 1

[0147] Preparation of Nanosilver-Graphene Composite Materials

[0148] Same as Example 1 above

[0149] Preparation of water-based UV-curable conductive ink

[0150] Binder: 20wt% homemade UV curable resin (1g), 11wt% 1,6-hexanediol diacrylate (0.55g)

[0151] Conductive filler: 60wt% (20wt% nanosilver, 40wt% nanosilver-graphene composite material) (3g)

[0152] Functional additives: 5wt% (BYK-1794 leveling agent, BYK-431 dispersant) (0.25g)

[0153] Photoinitiator: 4 wt% (2% Darocur 1173, 2% Irgacure 2959) (0.2 g)

[0154] A water-based UV-curable conductive ink was prepared according to the above ratio. After being evenly dispersed by a three-roll mill and a high-speed disperser, the ink was left to stand in a light-shielded place to defoam. The ink was then printed on a substrate and tested for its performance after UV curing.

[0155] Embodiment 6:

[0156] Preparation of acrylic acid modified epoxy resin prepolymer (EA)

[0157] Same as above-mentioned embodiment 1

[0158] Water-based UV resin synthesis

[0159] Same as above-mentioned Example 1

[0160] Preparation of Nanosilver

[0161] Same as above-mentioned embodiment 1

[0162] Preparation of Nanosilver-Graphene Composite Materials

[0163] Same as above-mentioned Example 1

[0164] Preparation of water-based UV-curable conductive ink

[0165] Binder: 20wt% homemade UV curable resin (1g), 11wt% 1,6-hexanediol diacrylate (0.55g)

[0166] Conductive filler: 60wt% (10wt% nanosilver, 50wt% nanosilver-graphene composite material) (3g)

[0167] Functional additives: 5wt% (BYK-1794 leveling agent, BYK-431 dispersant) (0.25g)

[0168] Photoinitiator: 4 wt% (2% Darocur 1173, 2% Irgacure 2959) (0.2 g)

[0169] A water-based UV-curable conductive ink was prepared according to the above ratio. After being evenly dispersed by a three-roll mill and a high-speed disperser, the ink was left to stand in a light-shielded place to defoam. The ink was then printed on a substrate and tested for performance after UV curing.

[0170] Embodiment 7:

[0171] Preparation of acrylic acid modified epoxy resin prepolymer (EA)

[0172] Same as above-mentioned embodiment 1

[0173] Water-based UV resin synthesis

[0174] Same as above-mentioned embodiment 1

[0175] Preparation of Nanosilver

[0176] Same as above-mentioned embodiment 1

[0177] Preparation of Nanosilver-Graphene Composite Materials

[0178] Same as above-mentioned embodiment 1

[0179] Preparation of water-based UV-curable conductive ink

[0180] Binder: 20wt% homemade UV curable resin (1g), 11wt% HDDA (1,6-hexanediol diacrylate) (0.55g)

[0181] Conductive filler: 60wt% (nanosilver-graphene composite material) (3g)

[0182] Functional additives: 5wt% (BYK-1794 leveling agent, BYK-431 dispersant) (0.25g)

[0183] Photoinitiator: 4 wt% (2% Darocur 1173, 2% Irgacure 2959) (0.2 g)

[0184] A water-based UV-curable conductive ink was prepared according to the above ratio. After being evenly dispersed by a three-roll mill and a high-speed disperser, the ink was left to stand in a light-shielded place to defoam. The ink was then printed on a substrate and tested for performance after UV curing.

[0185] Comparative Example 1

[0186] The "self-made water-based UV resin" in Example 4 was replaced with "water-based UV epoxy resin JZ-501 (Nanjing Jiazhong)".

[0187] Comparative Example 2

[0188] The "self-made water-based UV resin" in Example 4 was replaced with water-based UV acrylic resin MR2401 (Guangdong Keding)".

[0189] Comparative Example 3:

[0190] Replace the "nanosilver-graphene composite material" in Example 4 with "graphene / silver nanocomposite powder disclosed in patent (CN117711671A)".

[0191] Comparative Example 4

[0192] The "self-made water-based UV resin" in Example 4 was replaced with "water-based UV epoxy resin JZ-501 (Nanjing Jiazhong)", and nanosilver was not added, and the nanosilver was replaced with an equal amount of nanosilver-graphene composite material.

[0193] Comparative Example 5

[0194] The "self-made water-based UV resin" in Example 4 was replaced with "water-based UV epoxy resin JZ-501 (Nanjing Jiazhong)", and the nanosilver-graphene composite material was not added, and the nanosilver-graphene composite material was replaced with an equal amount of nanosilver.

[0195] Comparative Example 6

[0196] Replace the "nanosilver-graphene composite material" in Comparative Example 4 with "graphene / silver nanocomposite powder disclosed in patent (CN117711671A)".

[0197] Comparative Example 7

[0198] The "self-made water-based UV resin" in Example 4 was replaced by "water-based UV epoxy resin JZ-501 (Nanjing Jiazhong)", and the "nanosilver-graphene composite material" was replaced by "graphene / silver nanocomposite powder disclosed in patent (CN117711671A)".

[0199] The above examples and comparative examples are summarized in Table 1.

[0200] Table 1 Examples and Comparative Examples

[0201]

[0202]

[0203] Characterization and performance testing:

[0204] 1. Prepolymer EA infrared analysis

[0205] The prepolymer EA prepared in Example was subjected to infrared analysis, and the infrared spectrum was shown in FIG. Figure 2 , 3039cm in the picture -1The unsaturated C is the CH stretching vibration peak, 1623 cm -1 The peak of C=C stretching vibration is 1318 cm -1 The CH deformation vibration is at 782 cm -1 The peak of CH out-of-plane bending vibration is 3482 cm -1 The -OH characteristic peak is at , which indicates that the prepolymer intermediate EA is successfully prepared and the -OH contained in EA can undergo condensation reaction with -NCO.

[0206] 2. Infrared analysis of water-based UV resin

[0207] The water-based UV resin prepared in the example was subjected to infrared analysis, and the infrared spectrum showed Figure 3 , 3360cm in the figure -1 and 1552cm -1 The peak at 1730 cm is the NH absorption peak of carbamate. -1 The peak is C=O absorption peak, 1240cm -1 and 1163cm -1 The COC absorption peak is at 982cm, indicating that isophorone diisocyanate reacts with dimethylolbutyric acid to generate carbamate groups, and the water-based UV resin is successfully prepared. -1 The peak of C=C appears in A, but not in B, indicating that all the unsaturated bonds of the cured molecules have reacted.

[0208] 3. XRD analysis of nanosilver

[0209] XRD analysis was performed on the nanosilver prepared in the example, and the spectrum is shown in Figure 4 As shown in the figure, diffraction peaks appear at 2θ of 38.10°, 44.30°, 64.45°, and 77.70°. Analysis of the spectrum shows that the prepared nanosilver has an inter-cubic structure, which conforms to the standard spectrum of silver. The diffraction peaks appearing in the figure can correspond one by one to the (111), (200), (220), and (311) crystal planes of silver.

[0210] 4. XRD analysis of nanosilver-graphene composites

[0211] The nano silver-graphene composite material prepared in the example was subjected to XRD analysis, and the spectrum is shown in Figure 5 It can be seen that the diffraction peak of GO in the XRD spectrum of Ag-RGO is small, indicating that graphene oxide (GO) is successfully reduced to RGO. The -OH and -COOH groups on graphene oxide contain a large number of negatively charged ions, which attract Ag under the action of charge. +On the graphene oxide sheet structure, under the action of hydrazine hydrate, graphene oxide (GO) is reduced to reduced graphene oxide (RGO), silver ions are reduced to silver element, and RGO peak appears in the diffraction peak. The characterization structure shows that Ag-RGO is successfully prepared.

[0212] 5. Performance testing

[0213] The materials obtained in the examples and comparative examples were screen printed on a PET film and UV cured. The resistivity, hardness and adhesion of the obtained circuit were tested, and the results are shown in Table 2.

[0214] Table 2 Performance test results

[0215]

[0216]

[0217] Comparative Example 3 uses the graphene / nanosilver composite powder disclosed in the patent (CN117711671A) and the resistivity of its water-based ink is as high as 37×10 -8 Ω·m, reaching more than 4 times that of Example 4. The essential difference is that the patent uses graphene / nanosilver composite powder, while the present right uses nanosilver-graphene composite dispersion. The reason for the large difference in resistance between the two water-based conductive inks: the composite material is easy to mix evenly with other components of the water-based ink in the form of a dispersion, maintains good dispersibility, constructs more conductive paths, ensures that it does not aggregate and settle, and has good stability. If it is added to the aqueous slurry in the form of a powder, it is difficult to disperse, and the particles cannot construct a good conductive path in the resin matrix, resulting in a decrease in its conductivity. From the test results, it can be seen that the nanosilver, nanosilver-graphene composite material and modified resin in the scheme of the present invention work synergistically to improve the resistivity, hardness and adhesion of the material.

[0218] For Example 1 to Example 7, at a ratio of 60wt% of the conductive phase, the content of nanosilver gradually decreases, the content of the nano-graphene composite material gradually increases, and the hardness is from HB to B. The reason is that graphene has extremely high hardness, strength and wear resistance, and when nanosilver and graphene are combined, the two interact with each other to achieve a synergistic effect and enhance the overall hardness. The adhesion is reduced from level 0 to level 1, which may be because nanosilver has good surface activity and strong adhesion, and forms a strong bonding force with the resin substrate to improve adhesion. Among the nanosilver-graphene composite materials, the surface energy of graphene is low and the brittleness is large. As the proportion of its composite material increases, the adhesion of its water-based ink may decrease.

[0219] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0220] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a water-based UV curable conductive ink, characterized in that: The following steps are involved: S1, preparing modified waterborne UV resin, nanosilver and nanosilver-graphene composite materials respectively; S2, taking the prepared modified water-based UV resin, nanosilver and nanosilver-graphene composite material, mixing them with a photoinitiator, 1,6-hexanediol diacrylate and an additive to obtain a water-based UV curable conductive ink; Among them, the modified waterborne UV resin structure prepared by S1 is: From left to right, R1 and R2 are six-membered rings containing a central carbon atom and four connected methylene groups (CH2) to form a stable molecular skeleton. R3 is the bisphenol A group, which is the central part of the bisphenol A molecular structure and contains two aromatic groups and a secondary carbon bridge (two methyl groups -CH3).

2. The method for preparing the water-based UV curable conductive ink according to claim 1, characterized in that: The auxiliary agent in step S2 includes one or more of the following: gas silica, coupling agent KH-560, defoaming agent BYK-1794, dispersant BYK-431, leveling agent BYK-UV-3510, leveling agent BYK-333, DEGO-4100 wetting and leveling agent; the photoinitiator includes Darocur 1173 or Irgacure 2959.

3. The method for preparing the water-based UV curable conductive ink according to claim 1, characterized in that: The method for preparing the modified waterborne UV resin in step S1 comprises: (1) Preparing a modified epoxy resin prepolymer: adding a catalyst to a resin, mixing well, heating, slowly dropping a modifier into the system to carry out reaction I, cooling after the reaction is completed, and obtaining a modified epoxy resin prepolymer; (2) Synthesis of water-based UV resin: polycaprolactone diol, catalyst and chain extender are mixed and heated to carry out reaction II; after the reaction is completed, the temperature is lowered, pentaerythritol triacrylate and catalyst are added, and the temperature is kept to carry out reaction III; modified epoxy resin prepolymer is added and the reaction is continued until the isocyanate group content is constant; and post-treatment is performed to obtain a modified water-based UV resin.

4. The method for preparing the water-based UV curable conductive ink according to claim 3, characterized in that: In the method for preparing a modified waterborne UV resin, the resin in step (1) includes one or more of epoxy resin-E51, polyurethane, phenolic resin, and acrylic resin; wherein the epoxy resin includes one or more of bisphenol A epoxy resin, phenolic epoxy resin, and glycidyl ether epoxy resin; the catalyst includes one or more of tetrabutylammonium bromide, dibutyltin dilaurate, stannous octoate, organic lead, and organic zinc compounds; and the modified substance includes one or more of acrylic acid, polypropylene, polyurethane, bisphenol A epoxy resin, and silicone oil.

5. The method for preparing the water-based UV curable conductive ink according to claim 4, characterized in that: In the method for preparing a modified waterborne UV resin, the chain extender in step (2) includes one or more of dimethylolbutyric acid, ethylene glycol, propylene glycol, and stearic acid; the catalyst includes one or more of isophorone diisocyanate, sulfuric acid, sodium persulfate, pentaerythritol triacrylate, and dibutyltin dilaurate; the reaction II temperature is 70-80°C and the time is 2-3h; the reaction III temperature is 50-55°C and the time is 4-5h.

6. The method for preparing the water-based UV curable conductive ink according to claim 4, characterized in that: The post-treatment in step (2) of the method for preparing a modified water-based UV resin comprises: adding a diluent and mixing, then adding a neutralizing agent for neutralization, adding deionized water for uniform dispersion, and performing reduced pressure distillation to obtain the modified water-based UV resin; the diluent comprises one or more of acetone, methanol, and benzene; the neutralizing agent comprises one or more of triethylamine, ethylenediamine, and ferric chloride; and the neutralization time is 0.5-1h.

7. The method for preparing the water-based UV curable conductive ink according to claim 1, characterized in that: The method for preparing the nano silver-graphene composite material in step S1 comprises: Prepare graphene oxide into a suspension, add silver nitrate aqueous solution into the graphene oxide suspension and mix well, add a protective agent and a reducing agent while stirring in a constant temperature water bath, continue stirring, cool and centrifuge to obtain a precipitate, wash the precipitate with anhydrous ethanol, and disperse it in anhydrous ethanol to obtain a nanosilver-graphene dispersion.

8. The method for preparing the water-based UV curable conductive ink according to claim 7, characterized in that: The constant temperature water bath temperature is 50-65°C, and the stirring time is 0.5-1h; the centrifugation is performed at 12000-15000 rpm for 10-15min.

9. The method for preparing the water-based UV curable conductive ink according to claim 1, characterized in that: The method for preparing nanosilver in step S1 comprises: Slowly add silver nitrate aqueous solution to the mixed solution of protective agent and reducing agent, stir in a constant temperature water bath until the solution changes to gray, centrifuge to obtain precipitate, wash the precipitate with anhydrous ethanol, and disperse it in anhydrous ethanol to obtain a nanosilver dispersion.

10. The method for preparing the water-based UV curable conductive ink according to claim 9, characterized in that: The constant temperature water bath temperature is 50-65° C.; the centrifugation is performed at 12000-15000 rpm for 10-15 min; the reducing agent includes one or more of hydrazine hydrate, sodium sulfite, sodium hydroxide, sodium borohydride, and potassium iodide; and the protective agent includes one or more of polyvinyl pyrrolidone, sodium bisulfate, and alkaline ammonia water.

Citation Information

Patent Citations

  • Conductive silver paste doped with graphene / nano-silver composite powder and preparation method thereof

    CN117711671A

  • Polyurethane-modified flexible epoxy acrylic resin, preparation method of polyurethane-modified flexible epoxy acrylic resin, photo-curing identification oil ink and flexible printed circuit board

    CN108341921A

Cited By

  • Photocuring conductive ink

    CN119955347A

  • Preparation method of a nano silver conductive composite material

    CN120173374B

  • Conductive carbon oil and preparation method thereof

    CN120383847A